The association between age and nutritional status on developmental outcomes among children with down syndrome in Indonesia - Wulandari, Hajeng; Irwanto, Irwanto; Suryawan, Ahmad; Irmawati, Mira; Ariani, Ariani (Edelweiss Applied Science and Technology, 2025)
Children with Down syndrome pose a risk of nutritional problems and developmental delays. The aim of this study is to assess the association between age and nutritional status on development among children with Down syndrome in Indonesia. The study design was cross-sectional. The study group consisted of 55 children with Down syndrome from the POTADS community, an association of parents of children with Down syndrome in Surabaya, Indonesia. Development was assessed using the Developmental Scale for Children with Down Syndrome by Thomas L. Layton, Ph.D. Nutritional status was evaluated using the CDC Growth Charts for Children with Down syndrome. The results showed that the majority (60%) of subjects had normal nutritional status, and 92.7% exhibited delayed developmental status. There was no association between nutritional status and developmental status (p = 0.699), while age and developmental status showed a significant correlation (r = 0.382; p = 0.004). This study can serve as health information, especially for parents of children with Down syndrome, to increase awareness of developmental and nutritional delays in these children.